Strengthening the Implementation of Primary and Secondary Education Kartika Jaya Korem Education Foundation 063 Cirebon - Soegianto Soegianto; Kartimi Kartimi; Didin Nurul Rosidin; Ahmad Yani (Jurnal Abdisci, 2024)
Yayasan Kartika Jaya Korem 063 in Cirebon has long cared about education, so the foundation currently has two kindergarten schools, two elementary schools, junior high schools, vocational schools, and high schools. This community service activity is a form of service to the community as an advisory team that assists in the implementation of general government and development tasks. The results of this community service activity are coaching and supervision activities, financial management, educators and education staff, facilities and infrastructure, and payroll are all part of the education governance of the Kartika Foundation one-stop.